2018
DOI: 10.1096/fj.201701016r
|View full text |Cite
|
Sign up to set email alerts
|

Bcr‐Abl regulation of sphingomyelin synthase 1 reveals a novel oncogenic‐driven mechanism of protein up‐regulation

Abstract: Bcr-Abl (break-point cluster region-abelson), the oncogenic trigger of chronic myelogenous leukemia (CML), has previously been shown to up-regulate the expression and activity of sphingomyelin synthase 1 (SMS1), which contributes to the proliferation of CML cells; however, the mechanism by which this increased expression of SMS1 is mediated remains unknown. In the current study, we show that Bcr-Abl enhances the expression of SMS1 via a 30-fold up-regulation of its transcription. Of most interest, the Bcr-Abl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 88 publications
1
19
0
Order By: Relevance
“…It has also been reported that SMS1 was one of the downstream targets of BCR-ABL signaling. 88 BCR-ABL induces SMS1 transcription from an alternative transcription start site (TSS), leading to increased levels of SMS1 protein and SMS1-mediated proliferation. Indeed, BCR-ABL-positive K562 cells showed 70-fold up-regulation of SMS1 transcription as compared with BCR-ABL-negative HL-60 cells.…”
Section: Signal Transduction Is Regulated By Sms-mediated Ceramide/smmentioning
confidence: 99%
“…It has also been reported that SMS1 was one of the downstream targets of BCR-ABL signaling. 88 BCR-ABL induces SMS1 transcription from an alternative transcription start site (TSS), leading to increased levels of SMS1 protein and SMS1-mediated proliferation. Indeed, BCR-ABL-positive K562 cells showed 70-fold up-regulation of SMS1 transcription as compared with BCR-ABL-negative HL-60 cells.…”
Section: Signal Transduction Is Regulated By Sms-mediated Ceramide/smmentioning
confidence: 99%
“…Moreover, 4 deep deletions were identified as well as 17 CpG located on the two CpG islands and their shores, the methylation of which was correlated with SGMS1 downregulation in metastatic melanoma. SMS1 expression and activity are likely regulated by translational and post-translational mechanisms such as recently described in Bcr-Abl-expressing leukemia cells (Moorthi et al, 2018). Whereas key driver mutations have been identified in melanoma (Hodis et al, 2012), we found no correlation between mutation status and SL signature.…”
Section: Discussionmentioning
confidence: 89%
“…All constructs and their characteristics are listed in Tables 1 and 2. GFP transcripts carrying SGMS1 5 0 UTR IIb (IIb-GFP) or 7 (7-GFP) [28] were synthesized by GenScript USA Inc. (Piscataway, NJ, USA) and cloned into the pUC57 plasmid flanked by sequences for the restriction enzymes BamH1 (at 5 0 ) and Xba1 (at 3 0 ). The GFP sequence from Aequorea Victoria (Av, Jellyfish, Takara Bio, Mountain View, CA, USA, formerly Clontech) was utilized.…”
Section: Generation Of Mammalian Expression Constructsmentioning
confidence: 99%
“…All SGMS1 deletion/mutation constructs were obtained by PCR using the Phusion High-fidelity DNA polymerase (NEB Inc. Ipswich, MA, USA) according to manufacturer's instructions and, as template, the previously characterized wild-type transcript IIb-SGMS1 [28]. A list of all primers' combinations can be found in Table 3 while the sequences for IIb-SGMS1 and 7-SGMS1 can be found in Table 4.…”
Section: Generation Of Mammalian Expression Constructsmentioning
confidence: 99%
See 1 more Smart Citation